Rancang Bangun Schoolscape Berbasis QR Code Sebagai Upaya Penguatan Literasi Digital Berbasis Agama Islam di SD Negeri 1 Tegalrejo - Fajar Anshori, Lilik; Khuriyah, Khuriyah (Al-Wasathiyah: Journal of Islamic Studies, 2025)
This study aims to describe the design process of a QR Code-based Schoolscape as an effort to strengthen Islamic digital literacy at State Elementary School 1 Tegalrejo. The main problems in this study were students' low interest in reading Islamic material and the limited availability of engaging and contextual digital learning media. This study used a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the Spradley model through the stages of domain, taxonomy, componential, and cultural themes. The results indicate that Schoolscape development was carried out through needs identification, design, content development, testing, and implementation. Visual media with QR Codes placed at various points in the school were able to attract students' interest in accessing Islamic content independently and repeatedly. Teachers and parents played a crucial role in supporting this literacy process. These findings indicate that a QR Code-based Schoolscape can increase student engagement in a reflective, critical, and contextual Islamic digital literacy culture and can be a character-based learning strategy in the digital era.